2012
DOI: 10.1111/j.1755-3768.2011.02355.x
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma screening during regular optician visits: the feasibility and specificity of screening in real life

Abstract: ABSTRACT.Purpose: To determine the feasibility and specificity of glaucoma screening during regular optician visits. Methods: In four optician shops, glaucoma screening was offered to 400 consecutive visitors aged 45 years or above. If the visitor agreed to participate, an intraocular pressure measurement and -in those with a pressure below 25 mmHg -a frequency-doubling perimeter (FDT) C20-1 visual field screening test were performed. Those with an elevated pressure or at least one reproducibly abnormal test l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…The results of our study regarding the high proportion of referred individuals found not to have any eye disease at the hospital are similar to other recent studies. [12][13][14] However, the IOP thresholds suggested for referral in some previous studies were higher than those considered here. 13,14 Using the IOP threshold of ≥27 mmHg, suggested by Founti et al, 14 would have led to more than one patient in ten with a positive outcome being missed in our study.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The results of our study regarding the high proportion of referred individuals found not to have any eye disease at the hospital are similar to other recent studies. [12][13][14] However, the IOP thresholds suggested for referral in some previous studies were higher than those considered here. 13,14 Using the IOP threshold of ≥27 mmHg, suggested by Founti et al, 14 would have led to more than one patient in ten with a positive outcome being missed in our study.…”
Section: Discussioncontrasting
confidence: 72%
“…[8][9][10] There is currently no cost-effective screening method for glaucoma, and glaucoma suspects are often detected through opportunistic case finding by optometric practitioners (ie optometrists and opticians). Several studies over the past decade have reported that a high number of patients referred for glaucoma by optometric practitioners do not have any eye disease, [11][12][13][14] leading to unnecessary health care costs and patient stress. Recent studies have shown that it is possible to reduce the number of falsepositive referrals by introducing different glaucoma referral filtering services, 11,12,15 while others have proposed higher intraocular pressure (IOP) thresholds for IOP-only referrals.…”
Section: Introductionmentioning
confidence: 99%
“…Screening could be made more efficient by focusing on high-risk groups. However, currently known (nongenetic) risk factors are not strong enough to allow for screening limited to high-risk groups, as too many cases would be overlooked 101,119 Similarly, the currently known genes (from GWAS and other techniques) do not explain the observed heritability completely, and as such, screening based on genes is currently considered premature as well. 57 Knowledge on heritability drives further gene finding (aiming to annihilate the discrepancy between heritability and variance explained by known genes), ultimately aiming for efficient screening and personalized health care based on genetic profiles.…”
Section: Discussionmentioning
confidence: 99%
“…A specificity of 90% was reported for glaucoma detection by Dutch opticians, who performed Frequency‐Doubling Technology (FDT) and intraocular pressure measurements on 352 participants (Vries et al. ). A major strength of that study was the consecutive enrolment of participants; however, sensitivity was not reported.…”
Section: Discussionmentioning
confidence: 99%